The control system for special preparedness of cyclists - Колумбет, Олександр Миколайович; Колумбет, О. М.; Колумбет, Александр Николаевич; Kolumbet, Oleksandr M.; Kolumbet, A. N.; Дудорова, Людмила Юріївна; Дудорова, Л. Ю.; Дудорова, Людмила Юрьевна; Dudorova, Liudmyla Yu.; Бабіна, Наталя Олександрівна; Бабіна, Н. О.; Бабина, Наталья Александровна; et al. (IP Iermakov S. S., 2017)
Purpose: to develop a system for monitoring the level of special preparedness of cyclists (specialized in individual race for 4 km) on the basis of the indicators of the cardiorespiratory system. Material: The study involved bicyclists (n=14, age 18-22 years). Results: The step-increasing load to the full allows to determine the maximum functional opportunities of the body of cyclists. The coefficient of efficiency of the functioning of the cardiovascular system is equal to the ratio of the average distance value of the pulse to the maximum value of the pulse. Using the linear regression equation, it is possible to predict the magnitude of the pulse at a given speed of movement. Conclusions: It is possible to find out the individual characteristics of athletes with the help of an indicator of the effectiveness of the functioning of the cardiovascular system. One can compare the activity of the cardiovascular system of athletes of different qualifications, different age groups, gender, level of preparedness. The degree of realization of the functionality of cyclists is calculated by a special formula and serves to monitor the training and competitive process. The results of the studies make it possible to predict the result by evaluating the level of special physical preparation.

Мета: розробка системи моніторингу рівня спеціальної підготовленості велосипедистів (спеціалізуються на індивідуальній гонці на 4 км) на основі показників кардіореспіраторної системи. Матеріал: У дослідженні брали участь велосипедисти (n=14, вік 18-22 роки). Результати: ступінчасте збільшення навантаження в повному обсязі дозволяє визначити максимальні функціональні можливості організму велосипедистів. Коефіцієнт ефективності функціонування серцево-судинної системи дорівнює відношенню середнього значення відстані імпульсу до максимального значення пульсу. Використовуючи рівняння лінійної регресії, можна передбачити величину імпульсу при заданій швидкості руху. Висновки: З’ясувати індивідуальні особливості спортсменів можна за допомогою показника ефективності функціонування серцево-судинної системи. Можна порівняти діяльність серцево-судинної системи спортсменів різної кваліфікації, різних вікових груп, статі, рівня підготовленості. Ступінь реалізації функціональних можливостей велосипедистів розраховується за спеціальною формулою і служить для контролю за тренувальним і змагальним процесом. Результати досліджень дозволяють прогнозувати результат, оцінюючи рівень спеціальної фізичної підготовки.
Kolumbet A. N. The control system for special preparedness of cyclists / A. N. Kolumbet, L. Y. Dudorova, N. A. Babina, T. A. Bazulyuk, N. Y. Maximovich // Pedagogics, psychology, medical-biological problems of physical training and sports. – Vol. 21. - Iss. 6. – IP Iermakov S. S., 2017. - P. 266-271.
Keywords: cycling; pulse; control system; prognosis; success; цикл; пульс; система управління; прогноз; успіх; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports